Insomnia: Cara Yoga Mengatasi - I Gusti Bagus Wirawan; Ida Bagus Suatama; Ida Bagus Wiryanata (Jayapangus Press, 2019)
Modern style of living tends to accentuate the luxury that leads to the affection of physical pleasure and sensual pleasure. This will require more variety of needs that must be fulfilled and will have an impact on the work of the mind. If not there will be condition of lack of ability to control thoughts which can arise mental pressure, anxiety and eventually become stressful. If this condition is allowed, sleep will become difficult. People who have difficulty of sleeping are called insomnia. Therefore, on this study was carried out with the title